Update in Small Bowel Physiology: Part 2 - RJ Fingerote; S Churnratanakul; M Keelan; K Madsen; ABR Thomson (Canadian Journal of Gastroenterology)
The recent advances in clinically important diseases of the small intestine have been reviewed however, the basis for many of these clinical advances rests with important observations on alterations in the physiology of the small intestine, as well as mechanistic observations of alterations in small 1nrestinal function in models of human disease. In this review a summary of the past year's literature is presented which will draw attention to the considerable progress in small bowel physiology which will soon be translated into an improved understanding of the pathophysiology of a variety of intestinal disorders.